1991
DOI: 10.1002/syn.890080107
|View full text |Cite
|
Sign up to set email alerts
|

Rapid alteration of synaptic number and postsynaptic thickening length by NMDA: An electorn microscopic study in the occipital cortex of postnatral rats

Abstract: The N-methyl-D-aspartate (NMDA) receptor has been widely implicated in numerous activity-dependent models of neural plasticity, learning, and memory. The formation of new synapses is a major assumption of the neural basis of learning. The current research was conducted to determine whether NMDA receptor activation could induce synaptic formation and, if so, whether this ability would mirror developmental changes in NMDA receptors. Rats at various developmental ages were given a single intraperitoneal injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The reduction in the depth of the molecular layer and inhibition of developmental synaptogenesis that followed NMDA receptor antagonism is the opposite of the facilitatory effect on synaptogenesis that we previously observed with acute and/or chronic developmental administration of NMDA. Brief exposure to peripherally administered NMDA resulted in a rapid onset (within minutes) of synaptogenesis (Brooks et al, 1991), while chronic developmental administration of low doses of NMDA induced an increase in the depth of, and estimated total synapse number in, the occipital cortex molecular layer (Brooks et al, 1994). When considered along with the contrasting anatomical findings that followed increased NMDA receptor activity, the results of the current study suggest that the NMDA receptor plays an integral role in the process of developmental synaptogenesis and plasticity.…”
Section: Nmda Antagonist-induced Reductions In Synaptic Developmentmentioning
confidence: 53%
“…The reduction in the depth of the molecular layer and inhibition of developmental synaptogenesis that followed NMDA receptor antagonism is the opposite of the facilitatory effect on synaptogenesis that we previously observed with acute and/or chronic developmental administration of NMDA. Brief exposure to peripherally administered NMDA resulted in a rapid onset (within minutes) of synaptogenesis (Brooks et al, 1991), while chronic developmental administration of low doses of NMDA induced an increase in the depth of, and estimated total synapse number in, the occipital cortex molecular layer (Brooks et al, 1994). When considered along with the contrasting anatomical findings that followed increased NMDA receptor activity, the results of the current study suggest that the NMDA receptor plays an integral role in the process of developmental synaptogenesis and plasticity.…”
Section: Nmda Antagonist-induced Reductions In Synaptic Developmentmentioning
confidence: 53%
“…Elsewhere in the brain, activation of NMDA-type glutamate receptors is thought to mediate events as diverse as the outgrowth of axonal processes (Rashid and Cambray-Deakin 1992), synapse formation (Brooks et al 1991) and cell death (Nichol et al 1995). In accord with such findings, Bodnarenko and Chalupa (1993) have shown that the perturbation of glutamatergic function leads to abnormal stratification of dendrites of defined populations of retinal ganglion cells in the inner plexiform layer.…”
Section: Discussionmentioning
confidence: 89%
“…Direct injections of NMDA into the occipital cortex of 8-day-old rats (age at which there is a peak vulnerability to both NMDA injections and HI [61]) resulted in an increase in synaptic density (number of synapses) [62]. Conversely, NMDA receptor blockade resulted in a decrease in the total number of synapses [63], and was associated with deficits in learning and memory [77], thus confirming an important role of the NMDA receptor in synaptogenesis.…”
Section: Under Normal Conditionsmentioning
confidence: 92%
“…Synaptic plasticity (synaptogenesis) is the key factor in shaping the wiring pattern of the brain, and is responsible for the mechanism of learning and memory [62,63,76]. Direct injections of NMDA into the occipital cortex of 8-day-old rats (age at which there is a peak vulnerability to both NMDA injections and HI [61]) resulted in an increase in synaptic density (number of synapses) [62].…”
Section: Under Normal Conditionsmentioning
confidence: 99%
See 1 more Smart Citation